Screening of Cowpea Varieties for Relative Preference against Major Sucking Insect Pests - Yadav, Pooja; Hussain, Akhter; Yadav, Rajendra; Kumari, Heera; Yadav, Kamal (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during kharif (July-October) 2022 at the Agronomy Farm, Sri Karan Narendra College of Agriculture, Jobner to assess varietal resistance of some varieties of cowpea against major sucking insect pests. The aphid (Aphis craccivora Koch), leafhopper (Empoasca fabae (Harris)) and whitefly (Bemisia tabaci (Genn.)) were major sucking insect pests of cowpea and occuring in various parts of India and causing 20–40 % yield losses. Growing varieties resistant to insect pest is an ideal component of integrated pest management. The screening of available crop varieties helps to know the level of resistance in a particular variety so that farmers can cultivate it to attain higher yield even after pest infestation. In this study ten cowpea varieties (RC-19, GC-9040, KBC-9, Pant lobia-3, CPD-119, RC-101, Ajmer selection, KM-5, GC-3, CPD-3) were screened for their preference and susceptibility against the major sucking insect pests viz., aphid (Aphis craccivora Koch), leafhopper (Empoasca fabae (Harris)) and whitefly (Bemisia tabaci (Genn.)). None of the tested cowpea varieties were found completely free from insect pests infestation. However based on the level of insect pest incidence the varieties RC-101 and GC-3 were categorized as least susceptible to all three insect pests viz., aphid, leafhopper and whitefly. The varieties KBC-9, CPD-3, CPD-119, Pant Lobia-3 and GC-9040 were classified as moderately susceptible. While, the varieties RC-19, KM-5 and Ajmer Selection were identified as highly susceptible to aphid, leafhopper and whitefly.